Dentistry on the Bridge to Nanoscience and Nanotechnology - Salerno, Marco; Diaspro, Alberto (Frontiers in Materials, 2015)
Dentistry is the area of medical sciences that is most resistant to the introduction of the novel methods arisen from the development of nanoscience and nanotechnology in the last 20 years. Without moving on to science fiction like views pointing to times far ahead in the future, we show that the available nanoscale devices and processes of current science and technology, partly inherited from the areas of microscopy and microelectronics, have already proven to be useful for research and development in different fields of dental research. To this goal, we review some results obtained in the last few years at our Institute in the area of dental materials and their characterization, which showed successful application of our background in microscopy and nanoengineering.